Health related quality of life and self esteem of substance users in Bangladesh (Dhaka University Journal of Biological Sciences, 2015)
This study explored health related quality of life (HRQoL) of substance users (SUs) in Bangladesh in comparison with healthy control groups (CGs). Additionally, role of self esteem and sex on HRQoL was investigated. A trained assistant counselling psychologist measured HRQoL and self‐esteem of 120 SUs and 120 CGs using SF‐36 questionnaire and Rosenberg Self Esteem scale, respectively. SUs were mostly male (79.2%) from middle socioeconomic class (94%). SUs scored poorer in all domains of SF‐36 than the CGs. The magnitude of the effect size was largest for the role physical (effect size = –0.79), general mental health (effect size = –0.76) and social functioning (effect size = –0.73) subscale. Overall mental health was lower than physical health (effect size = –0.897). Males in both groups were better in four sub‐scales while females reported less role limitation due to physical and emotional problems. Self esteem moderated HRQoL of both group with slightly higher magnitude for SUs. HRQoL of SU of Bangladesh was lower than the study population.Dhaka Univ. J. Biol. Sci. 24(2): 199-207, 2015 (July)